2018
DOI: 10.1016/j.biomaterials.2018.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Muscle stem cell intramuscular delivery within hyaluronan methylcellulose improves engraftment efficiency and dispersion

Abstract: Adult skeletal muscle tissue harbors the capacity for self-repair due to the presence of tissue resident muscle stem cells (MuSCs). Advances in the area of prospective MuSC isolation demonstrated the potential of cell transplantation therapy as a regenerative medicine strategy to restore strength and long-term regenerative capacity to aged, injured, or diseased skeletal muscle tissue. However, cell loss during ejection, limits to post-injection proliferation, and poor donor cell dispersion distal to the inject… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…169,170 Davoudi et al reported that using an injectable hyaluronan-based and methyl cellulose-based hydrogel for intramuscular delivery significantly improved proliferation of MDSCs, retained their presence at the site of injury, and showed a significant benefit over injection-based administration. 171 In another study, Sleep and colleagues utilized a nanofiber-containing self-assembled hydrogel to guide the alignment and engraftment of SCs into injured tissue. 172 External stimulation of cell function especially holds true for MSCs, which respond to a variety of biophysical cues.…”
Section: Drawbacks and Limitationsmentioning
confidence: 99%
“…169,170 Davoudi et al reported that using an injectable hyaluronan-based and methyl cellulose-based hydrogel for intramuscular delivery significantly improved proliferation of MDSCs, retained their presence at the site of injury, and showed a significant benefit over injection-based administration. 171 In another study, Sleep and colleagues utilized a nanofiber-containing self-assembled hydrogel to guide the alignment and engraftment of SCs into injured tissue. 172 External stimulation of cell function especially holds true for MSCs, which respond to a variety of biophysical cues.…”
Section: Drawbacks and Limitationsmentioning
confidence: 99%
“…Primary myoblast cell lines were generated from Tg(CAG-EGFP) hindlimb muscles and the cultures were maintained as described before ( Davoudi et al. , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Progress towards tackling this obstacle has been made with the generation of injectable, encapsulating, 3D biomaterials that mirror the structural architecture of muscle and can be loaded with a cocktail of growth factors to enhance transplantation efficiency of MuSCs. Examples have included synthetic macromers 30 , bioactive hydrogels [31][32][33][34] and other biomimetic scaffolds 35 (reviewed by Wolf et al 36 ) An impressive illustration of this approach was by Han et al 30 who through a series of iterative design optimization steps, recently engineered a fully synthetic, degradable, poly(ethylene glycol) (PEG)-4MAL hydrogel functionalized with integrin-binding Arg-Gly-Asp (RGD) peptides. When co-injected with MuSCs, this biomaterial resulted in boosted MuSC proliferation, survival and in vivo engraftment into dystrophic and aged mouse skeletal muscle.…”
Section: Biomaterials Technologies For Muscle Repairmentioning
confidence: 99%